Strategy to Maintain Automotive Battery Retail Business Performance at PT Rezeki Berkah Bahagia: A Review of Entrepreneurial Orientation Dimensions - Muhammad Rifqi Mafatikhul Huda; Agung Winarno; Ludi Wishnu Wardana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Micro, small, and medium enterprises (MSMEs) are businesses owned by an individual, household or business entity as determined by Law no 8. 2008.MSMEs have an important role in advancing economic growth in Indonesia. The purpose of this study is to determine the strategy to maintain the performance of the Automotive Battery retail business at PT Rezeki Berkah Bahagia: A Review of the Dimensions of Entrepreneurial Orientation. This study uses a qualitative type, data sources in the form of interviews. Data analysis was carried out based on the Miles and Huberman model, which includes the stages of data collection, reduction, presentation, and drawing conclusions. To ensure the validity of the data. The results show that the strategy to maintain the performance of the automotive battery retail business at PT. Rezeki Berkah Bahagia is strongly influenced by the application of entrepreneurial orientation dimensions that include innovation, risk taking and proactivity. These three dimensions have been proven to contribute significantly to the company's resilience and competitiveness amidst intense competition and changing market needs. Innovation is implemented in the form of service development, utilization of digital technology, and improving the quality of products and services to customers.